Analisis Tingkat Pengetahuan, Sikap dan Perilaku Peternak Unggas Terhadap Upaya Pencegahan Penyakit Flu Burung - Adji Santoso Dradjat; Made Sriasih; Rusman Effendi (Faculty of Animal Husbandry, University of Mataram, 2016)
The aim of this research was to describe and to correlate knowledge, attitude and practice (KAP) of thepoultry breeders in preventing Avian Influenza (AI). This research used face-to-face interview, cross sectionaldesign study with a questionnaire for 100 respondentsand data were analyzed with Rho Spearman. The resultshowed that 82% of respondents washed their hands with soap after handling poultry but only 5% ofrespondents used mask when contacting with poultry. Chickens were kept by respondents most. The cagelocation near to the house accounted for 71%, most of respondents cleaned the cage routinely but there were11% of respondents who did not keep their poultry into the cage. All respondents revealed that the poultrywere not vaccinated periodically. It was about 37.3% of respondents burned dead poultry, and 55.2% and 22.4% buried and throw away to the river respectively. They disagreed with stamping out accounted for 48% andonly 16% of respondents agreed to sell their unhealthy poultry. No respondents informed to the authority ofsub-village when suddent death of the chickens was found. Respondent’s knowledge, attitude and practicewere suffient in preventing Avian Influenza and there was significant correlation between knowledge, attitudeand practice (P<0,05).